Basalt carbon hybrid composite for wind turbine rotor blades: A short review - Mengal, A.N. (Trans Tech Publications Ltd, 2014)
Wind turbine blades are the major structural element and highest cost component in the wind power system. Modern wind turbine blade sizes are increasing, and the driving motivation behind this is to increase the efficiency and energy output per unit rotor area, and to reduce the cost per kilowatt hour. However due to the increase in size the material selection for wind turbine has become critical and complex. To achieve the desired materials to improve the design of wind turbine blades several factors such as high fatigue strength, less weight, less cost and potential of recycling must be focused. Basalt fiber is a relative newcomer to fiber reinforced polymers and structural composites. Basalt fiber with their excellent mechanical properties represents an interesting alternative composite material for modern wind turbine blades. Some manufacturers claim that basalt fiber has similar or better properties than S-2 glass fiber and it's cheaper than carbon fiber. Basalt fiber together with carbon fiber are the most advanced and interesting area of hybrid technologies. This paper reviews extra ordinary properties of basalt fiber over other fiber reinforced composites and highlight how the basalt special properties together with carbon fiber will reduce the weight and cost of wind turbine blades while improving their performance. This paper also demonstrates why the basalt carbon hybrid composite material will be an ideal alternative for the wind turbine rotor blades. Â© (2014) Trans Tech Publications, Switzerland.